PROTOTIPE LITERASI INFORMASI BERBASIS WEB SEBAGAI UPAYA PENINGKATAN KEMAMPUAN LITERASI SISWA MAN INSAN CENDEKIA - Kurnianingsih, Indah; Ekadiana, Nova; Deliasari, Arieni (Edulib, 2017)
Abstract. Information Literacy (IL) Program is a library program that aims to improve the ability of library users to recognize when information is needed and have the ability to locate, evaluate, and use effectively the needed information. Information literacy learning is essential to be taught and applied in education from the beginning of the school so that students are able to find and organize information effectively and efficiently particularly regard to the school assignment and learning process. At present, various educational institutions began to implement online learning model to improve the quality of teaching and research quality. Due to the advancement of information technology, the information literacy program should be adjusted with the needs of library users. The purpose of this study was to design web-based information literacy model for school library. This research conducted through several stages which are: identifying the needs of web-based IL, designing web-based IL, determining the model and the contents of a web-based IL tutorial, and creating a prototype webbased IL. The results showed that 90,74% of respondents stated the need of web-based learning IL. The prototype of web-based learning IL is consisted of six main units using combination of the Big6 Skills model and 7 Concept of Information Literacy by Shapiro and Hughes. The main fiveth units are Library Skill, Resource Skill, Research Skill, Reading Skill, and Presenting Literacy. This prototype web-based information literacy is expected to support the information literacy learning in a holistic approach.